EMBRYONIC AND LARVAL DEVELOPMENT OF THE PRAWN MACROBRACHIUM KISTNENSIS - Nagabhushanam, R; Kulkarni, M Y (Indian Journal of Fisheries, 2011)
The embryonic and larval development of Macrobrachium kistnemis isdescribed in detail. The larvae were reared in the laboratory, These were liberatedby ovigerous females on the twentyninth day during night. The period of embryonicdevelopment was found to be 29 to 30 days. Four zoaeal stages and the postlarvalare described and illustrated. The larval development was complete in the laboratoryand the larva entered into the juvenile adult condition in 7-11 days afterhatching. The duration of the various zoaeal stages varied between 24 h and fourdays, and the average period was 3-2 days.